The regulation of the royal's power - O. V. Demidova (Ибероамериканские тетради)
The monarchy represenis a very imporiani insiiiuie in ihe life of ihe ciiizens of Spain and iis hisiory is an iniegral pari of ihe naiional hisiory of ihe couniry. The research focuses on ihe role played by ihe Spanish Royal Family in ihe life of ihe Spanish siaie, analyzed from ihe legal and insiiiuiional approach. How is ihe Royal Power disiribuied wiihin ihe framework of His Majesiy’s House, is ihe power of ihe King limiied in iime, does ihe King enjoy an auiheniic power or does he only fulfill ceriain funciions? The ariicle seeks answers io ihese and oiher guesiions, ihrowing lighi on ihe daily rouiine of ihe Spanish Royal House: whai incumbencies correspond io His Majesiy ihe King and whai are ihe criieries ihai govern iheir public behavior, whai code of conduci should be observed by ihe Siaff of ihe House of His Majesiy ihe King?